1976
DOI: 10.1002/srin.197603776
|View full text |Cite
|
Sign up to set email alerts
|

Die Wärmeausdehnung kubisch‐flächenzentrierter Eisenlegierungen

Abstract: Dilatometrische Messungen zwischen −200 und 500 °C an Eisen‐Nickel‐, Eisen‐Mangan‐ und Eisen‐Mangan‐Nickel‐Legierungen. Einfluß von Kohlenstoff, Chrom und Kupfer auf Wärmeausdehnung und magnetische Eigenschaften. Ermittlung der Volumenmagnetostriktion an den ferromagnetisch und antiferromagnetisch geordneten Legierungen. Vergleich der relativen Längenänderung zwischen 20 und −200 °C bei verschiedenen Werkstoffen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Rhodes and Thompson 43 suggested that the stacking -fault energy values of the Schramm and Reed analysis were too large, considering additional weak-beam electronmicroscopy data. Weak-beam electron microscopy measurements by Bampton, Jones, and Loretto 44 confirmed that the least-square analysis of Schramm and Reed produced stacking-fault energies that were too large. From measurements of individual nodes, they estimated a data spread of ± 25%.…”
Section: Stacking-fault Energymentioning
confidence: 91%
See 3 more Smart Citations
“…Rhodes and Thompson 43 suggested that the stacking -fault energy values of the Schramm and Reed analysis were too large, considering additional weak-beam electronmicroscopy data. Weak-beam electron microscopy measurements by Bampton, Jones, and Loretto 44 confirmed that the least-square analysis of Schramm and Reed produced stacking-fault energies that were too large. From measurements of individual nodes, they estimated a data spread of ± 25%.…”
Section: Stacking-fault Energymentioning
confidence: 91%
“…Fujikuma et al 44 measured stackingfault probabilities for an Fe-18Cr-lONi-8Mn alloy. They reported a minimum at about 0.15N; a slight increase at lover N contents, and a rapid increase at higher N. Thus, all three sets of measurements appear to be consistent: the stacking -fault energy increased slightly with N contents up to about 0.20 vt.%; it decreased substantially for higher N contents.…”
Section: Stacking-fault Energymentioning
confidence: 99%
See 2 more Smart Citations